Privatization policy - Learning from best practice and mimicking policy fashions? Empirical evidence from the telecommunication sector - Carina Schmitt (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2010)
This working paper examines the question whether the privatization of network based utilities results from policy diffusion across the OECD world, and if so which diffusion mechanisms have been relevant. Therefore, a completely new panel data set on privatization in the telecommunication sector is introduced which offers a unique opportunity for a broad-based international comparison. The sample includes 18 OECD countries between 1980 and 2007. In order to analyze the hypotheses empirically, spatial econometric techniques are used. The paper shows that governments do not implement privatization policies independently of each other. Second, the relevant spatial interdependencies are determined by geographical proximity and economic relationships. Countries clearly tend to privatize when trading partners or countries that are geographically close to them do so. Third, there is no evidence that governments adopt policies of countries with similar cultural backgrounds or simply where privatization leads to the intended outcomes at the company level. Fourth, the diffusion of privatization policy is highly influenced by the openness of the economy. Open economies are more receptive to diffusion mechanisms than economies that are only moderately involved in the international market. – – Dieser Beitrag untersucht die Frage, ob die Privatisierung netzbasierter Infrastruktursektoren in der OECD-Welt auf Politikdiffusion zurückzuführen ist und wenn ja, welche Diffusionskanäle von Relevanz waren. Es wird ein neuer Paneldatensatz zu Privatisierung im Telekommunikationssektor vorgestellt, der einen umfassenden internationalen Vergleich von Privatisierungspolitiken ermöglicht. Untersucht werden 18 OECD-Staaten im Zeitraum zwischen 1980 und 2007. Zur empirischen Überprüfung werden Schätzverfahren und Methoden der Räumlichen Ökonometrie angewandt. Der Beitrag zeigt, dass Interdependenzen zwischen Staaten bei der Analyse von Privatisierungspolitik berücksichtigt werden müssen und dass Regierungen Privatisierungspolitik nicht unabhängig voneinander implementieren. Zweitens sind die Interdependenzen insbesondere durch räumliche und wirtschaftliche Nähe geprägt. Länder tendieren zur Privatisierung, wenn wichtige Handelspartner oder Länder Nachbarländer dies tun. Drittens konnten keine empirischen Hinweise gefunden werden, dass Regierungen privatisierungspolitischen Maßnahmen von Ländern mit einem ähnlichen kulturellen Hintergrund folgen oder die Privatisierungspolitik nachahmen, mit der auf Unternehmensebene die gewünschten Effekte erzielt werden konnten. Viertens ist die Diffusion von Privatisierungspolitik stark von der Offenheit der Volkswirtschaft beeinflusst. Offene Volkswirtschaften sind stärker für Diffusionsmechanismen empfänglich als jene, die nur sehr moderat in den internationalen Markt eingebunden sind.
Keywords: 330; Privatisierung; Telekommunikationspolitik; OECD-Staaten